1989
DOI: 10.1016/0010-0277(89)90030-9
|View full text |Cite
|
Sign up to set email alerts
|

The development of separability in visual perception

Abstract: Kolinsky, R., 1989. The development of separability in visual perception. Cognition, Under conditions that do not allow focused attention, reports of illusory conjunctions (i.e. errors that wrongly recombine the features of different objects) constitute evidence of the separate registering of features at an early processing level. The occurrence of illusory conjunctions was used to determine whether there is preattentive analysis of component dimensions (colour and form) and of parts of shapes (triangles and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Yet, this claim remains to be demonstrated empirically. At least in the visual domain, some evidence has been found that dimensions described as integral by standard criteria, such as using those of Garner, have to be considered as separable when using a more indirect criterion of separability (Kolinsky, 1989), such as the occurrence of illusory conjunctions (Treisman, 1986;Treisman & Schmidt, 1982). Further exploitation of these concepts and methods in the music domain is certainly worthwhile, for its usefulness has been fully demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…Yet, this claim remains to be demonstrated empirically. At least in the visual domain, some evidence has been found that dimensions described as integral by standard criteria, such as using those of Garner, have to be considered as separable when using a more indirect criterion of separability (Kolinsky, 1989), such as the occurrence of illusory conjunctions (Treisman, 1986;Treisman & Schmidt, 1982). Further exploitation of these concepts and methods in the music domain is certainly worthwhile, for its usefulness has been fully demonstrated in the present study.…”
Section: Discussionmentioning
confidence: 70%
“…First, individual lines of triangles were shown to be analyzed preattentively. Since they conjoin with other forms to create ICs as often as spatially separate segments, they do not seem to "stick together" at all (Kolinsky, 1989;Treisman & Paterson, 1984). Second, early extraction of some kind of emergent or configurational information may account for the preservation of the relative position of the triangle segments."…”
Section: Illusory Conjunctionsmentioning
confidence: 99%
“…More precisely, given the possibly large number of simple misperceptions, ICs are estimated by comparing target FDs made on target-absent experimental trials, in which all the information necessary to perceive the target is present, although not in the same object, with FDs made on target-absent control trials, in which one of the target's attributes is missing. As can be seen in Figure 1, target-absent experimental displays always contained two differently oriented forms (either triangles, as in Figures Yet, even in such a simple detection situation, both CDs and ICs may result from decision bias (Kolinsky, 1988(Kolinsky, , 1989Treisman & Souther, 1986). Thus, rather than directly comparing raw FD and CD scores with regard to laterality effects, we also used the signal detection theory bias-free index of discriminability, d' (see, e.g., Green & Swets, 1966).…”
mentioning
confidence: 98%
See 2 more Smart Citations